2018
DOI: 10.1155/2018/7031867
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SiC Nanoparticle Reinforcement on FSS Welded 6061-T6 Aluminum Alloy

Abstract: The current research focuses on the mechanical properties and the microstructural behavior of friction stir spot-welded 6061-T6 aluminum alloy reinforced with SiC nanoparticles. Weld samples are produced with and without the addition of SiC nanoparticles to the joint. The microhardness and lap shear strength of the joints are investigated. The cross section of welds and the fracture surfaces are studied by a stereo zoom microscope. Microstructure and distribution of reinforced particles in the stir zone are ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Studies also showed the amount of incorporating the nanoparticles have a greater influence on the mechanical properties of the joint. For instance, a study showed that, increased volume fraction of SiC nanoparticles in AA6061 alloy improved the hardness profile and tensile strength, which is shown in Figure 12 [72]. This improvement was mainly due to the absence of interface gap between the base metal and weld nugget.…”
Section: Effect Of Carbide Nanoparticles On Mechanical Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies also showed the amount of incorporating the nanoparticles have a greater influence on the mechanical properties of the joint. For instance, a study showed that, increased volume fraction of SiC nanoparticles in AA6061 alloy improved the hardness profile and tensile strength, which is shown in Figure 12 [72]. This improvement was mainly due to the absence of interface gap between the base metal and weld nugget.…”
Section: Effect Of Carbide Nanoparticles On Mechanical Propertiesmentioning
confidence: 96%
“…In addition to the type of reinforcing nanoparticle, the volume of nanoparticle addition also aids in grain size formation [31,71]. For instance, FSW of AA6061 (i.e., alloy similar to AA6082 alloy) with SiC nanoparticles showed that increased volume fraction of nanoparticle reinforcement (from 14% to 29%) led to homogeneous dispersion, causing reduction in grain size as well as improvement in the mechanical properties [72].…”
Section: Effect Of Carbide Nanoparticles On Microstructural Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve a homogeneous dispersion of nanofillers in the matrix, it is inevitable to use an expensive surface functionalization process [22,23,24]. Dispersion behavior of nanofillers in the matrix can be investigated through various techniques like Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The other joints (1%, 3%, 4%, 5% with Al 2 O 3 and 1%, 3%, 4%, 5% with SiC) depicts slightly lower UTS values due to the reduced or increased quantity of wt% of the reinforcements, particularly when the wt% of the SiC is increased beyond 3% the shrinkage happens on the surface of the weld thus leading to decrease in strength of the joints [18]. Therefore, the morphology of the evenly distributed SiC particulates in Stir zone has greater impact on the bonding of interlock joints slightly higher than Al 2 O 3 , as shown in Fig.…”
Section: Tensile Strength Of Interlock Lap Joints With Reinforcementsmentioning
confidence: 98%